RISK FACTORS OF UMBILICAL CORD PATHOLOGY AND FACTORS OF NEGATIVE PERINATAL CONSEQUENCES AND NEWBORN INCIDENCE - Б. Дубецький; О. Макарчук; О. Андрієць; М. Римарчук (Неонатологія, хірургія та перинатальна медицина, 2023)
According to literature sources, the real frequency of many umbilical cord pathologies differs significantly from the statistical data indicated by researchers in their works (from 15% to 38%). The implementation of a system of diagnostic and treatment and preventive measures, based on mandatory antenatal and postnatal assessment of the features and characteristics of the umbilical cord, allows to improve perinatal outcomes and reduce perinatal morbidity. The aim of the work was to identify the main risk factors of umbilical cord pathology and negative perinatal consequences; to develop elements of standardization of antenatal and postnatal diagnosis of umbilical cord pathology. Research materials and methods. A retrospective assessment of medical documentation data (3,280 individual medical records of pregnant women) made it possible to establish the frequency of umbilical cord pathology in the population. In the future, a more detailed extended antenatal and postnatal examination of the umbilical cord and placenta after delivery was carried out in 637 patients of reproductive age with pregnancy complicated by pathology of the umbilical cord (main group). The control group was formed by 40 patients with an uncomplicated course of pregnancy and live birth of full-term healthy children. The study was conducted taking into account the main principles of the Helsinki Declaration on Biometric Research and the powers of the GCH ICH, in accordance with biometric norms with compliance with the principles of confidentiality and ethics (excerpt from protocol No. 128/22 of the meeting of the Bioethics Commission dated September 29, 2022, Ivano-Frankivsk National Medical University, Ministry of Health of Ukraine). Data analysis was performed using the Statistica 7.0 package of statistical programs (StatSoftInc., USA). The association of independent variables with the condition being studied is presented as odds ratio (OR) and 95% confidence interval (CI). The materials of the article are the result of the research of the complex research work fragment of the Department of Obstetrics and Gynecology named after I.D. Lanovyi of the Ivano-Frankivsk National Medical University: “Development of diagnostic tactics and pathogenetic substantiation of effective methods of preserving and restoring reproductive potential and improving parameters of a woman’s quality of life in obstetric and gynecological pathology” (state registration number 0121U109269, implementation dates 2021-2026 ), the author is a co-executor of the topic. Research results and their discussion. The following data were noted: an excess of the population norm of the length of the umbilical cord, a high proportion of eccentric and marginal insertion of the umbilical cord (22.14%) and umbilical cord coiling (33.28%), a decrease in the proportion of the reference limits of the umbilical cord tortuosity index (15.86%), in 56.7% of observations, the specific gravity of the umbilical cord was lower. Probable risk factors for umbilical cord pathology with a predominance of age over 35 years, nicotine addiction in pregnant women, multiple fertility, use of IVF programs, change in the amniotic fluid index, overweight and obesity, other clinical conditions associated with metabolic disorders (gestational diabetes, insulin resistance) were identified. Conclusion. The share of the umbilical cord pathology both in the isolated type and in the combination of characteristic features of the umbilical cord is 40.98%. The increase in the risk of negative perinatal consequences has a close relationship with the umbilical cord pathology and the combination of different types of pathology, as well as the addition of gestational complications, which allows for the formation of screening programs and optimization of the diagnostic algorithm.